Bioenergetika legkoatleticeskogo bega v pokazateljach energeticeskoj stimosti - Lazareva, E. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The purpose of this paper was to describe the bioenergetics of running in the terms of energetic cost. The elite athletes (sprinters and stayers) took part in the experiment. The aerobic power output doesn't contribute to the general power production in running with tlim<27 s. The alactate and glycolic power production achieves its maximum level with tlim = 40 s (distance 300 m) and then it reduces. The speed of the power production decreases as tlim increases. When tlim = 9.5 min (distance 3000 m) the intensity of the energy output in anaerobic process is 1/50, but the speed of the energy output in aerobic process slowly increases with the increase of tlim (when tlim = 9.5 min achieves maximum in 280 cal/rg·min). On long distances of running the amount of energy, produced as a result of anaerobic processes is low, because of that these distances have aerobic trend by nature. If the increase of power of exercises takes place on long distances, it will be provided already by anaerobic mechanisms.